Income distribution and endogenous dollarization (Capítulo) - Castillo, Paul (2016)
In this chapter we combine portfolio decisions of individuals and invoicing decisions of firms into a general equilibrium cash-in-advance monetary model to explain the pattern of dollarization across types of goods. This framework provides a theoretical link between asset and transaction dollarization. We find that transaction dollarization depends positively on asset dollarization. The exact relationship between transaction and asset dollarization is shaped by the income distribution. Furthermore, for partial asset dollarization, luxury goods, those associated to high-income customers, are endogenously priced in foreign currency, while high priority goods, those associated to low-income customers, are priced in domestic currency. When dollarization is partial, asset dollarization is always higher than transaction dollarization.